Proses Produksi dan Pengendalian Mutu Bahan Baku Susu Pasteurisasi di CV. Cita Nasional Getasan Semarang - Sholikah Indriani; Elsya Ermawati; Siti Lukluatul Jannah; Yatin Eka Wati; Muflikhatul Munawaroh; Safitri Injarsari; Muhamad Jalil (Symbiotic: Journal of Biological Education and Science, 2022)
Milk is a good food for consumption because it contains good and perfect nutrients. Fresh cow's milk is widely consumed by the community, that's why the quality must be maintained during processing so that people can consume it safely. The purpose of this research is to explain how to process pasteurized milk and how to maintain the quality of pasteurized milk. This research was conducted at CV. National Citadel in November. The data collection technique used in this study was carried out by observation, interviews, and FGD methods. The results showed: (1) Pasteurized milk processing in CV. National Cita through several stages, namely mixing, homogenization, pasteurization, filling and packaging; (2) How to maintain the quality of pasteurized milk in CV. National Cita has 7 stages of testing: (a )organoleptic test (b) milk specific gravity test (c) pH and temperature test (d) alcohol test (e) fat content test (f) milk consistency test ( g) tatl solid and non fat solid test (h) MBRT test; (3) raw materials in the form of forage and concentrates